Soil Transmitted Helminths (STH) Infection Related Body Mass Index in Elementary School Students, Sukawinatan Landfill, Palembang City - Indri Ramayanti; Asmarani Makmun (HM Publisher, 2018)
ABSTRACT Introduction The age of Primary School Children are the group most often affected by worm infections with a prevalence of more than 60%. Worm infection can cause a decrease in health conditions, Body Mass Index (BMI), intelligence and productivity of sufferers so that economically causes a lot of losses and decreases in the quality of human resources. Aims of Study The purpose of this study was to determine the relationship of infection with Soil Transmitted Helminths (STH) with the Body Mass Index (BMI) in the children of Elementary School ( SDN 188), Sukawinatan Landfill, Sukarame District, Palembang City. Methods This research is an analytic observational study with a cross-sectional approach. The population consisted of all children of SDN 188 Sukarame Subdistrict, Palembang City, 109 people who were selected by consecutive sampling. Examination of helminthiasis infection was obtained by taking faecal samples on the subject and then examined by laboratory with Kato-Katz method and Body Mass Index (BMI) through anthropomometric measurements of height and weight. The analysis carried out was univariate descriptively and bivariately by Chi-square test. Results There were found 27 (24.8%) children who were positive for helminthiasis and from the results of the bivariate test there was no correlation between STH infection and BMI (p> 0.05). Conclusion there was no significant relationship between infection with Soil Transmitted Helminths (STH) and the Body Mass Index (BMI) of primary school age children around the Sukawinatan landfill in Palembang. Keywords: STH Infection, Body Mass Indeks, Landfiil Area